PROFESSIONAL EXAMINATIONS: A DEPARTMENT FOR STUDENTS OF ACCOUNTING. - Chamberlain, Henry T. (The Accounting Review, 1952)
The article presents problems that were prepared by the Board of Examiners of the American Institute of Accountants and were presented as the first half of the May, 1952, C.P.A. examination in accounting practice. The candidates were required to solve problems 1 and 2 and either problem 3 or problem 4. The time allowed was four and a half hours. Some of the questions included in the paper are. The board of directors of the Nelson Company authorized a $1,000,000 issue of 5% convertible 20-year bonds dated March 1, 1948. Interest is payable on March 1 and September 1 of each year. The conversion agreement provides that until March 1, 1953 each $1,000 of bonds may be converted into 6 shares of $100 par value common stock and that interest accrued to date of conversion will be paid in cash. After March 1, 1953 the bonds are convertible into shares of common for each $1,000 of bonds. The company sold the entire bond issue on June 30, 1948, at 98 and accrued interest. Deferable costs incurred in making the sale amounted to $8,320. The company adjusts its books at the end of each month and closes them on December 31 of each year. Interest is paid as due. On February 1, 1950, a holder of $20,000 of bonds converts them into common stock.